Emerging role of exosomes as biomarkers in cancer treatment and diagnosis. (January 2022) - Hanjani, Niloofar Asadi; Esmaelizad, Nazanin; Zanganeh, Saba; Gharavi, Abdulwahab Teflischi; Heidarizadeh, Pegah; Radfar, Maryam; Omidi, Fateme; MacLoughlin, Ronan; Doroudian, Mohammad
Graphical abstract: The structure and content of exosomes. Highlights: Exosomes play critical roles in regulating metastasis, and tumour progression. Identifying their cargos can develop into exosome-based cancer therapy. Exosomes are a promising strategy to employ as biomarkers providing useful information to be used as cancer diagnosis. Exosome-based cancer therapy are becoming increasingly employed in clinical practice. Abstract: Cancer is a leading cause of death worldwide and cancer incidence and mortality are rapidly growing. These massive amounts of cancer patients require rapid diagnosis and efficient treatment strategies. However, the currently utilized methods are invasive and cost-effective. Recently, the effective roles of exosomes as promising diagnostic, prognostic, and predictive biomarkers have been revealed. Exosomes are membrane-bound extracellular vesicles containing RNAs, DNAs, and proteins, and are present in a wide array of body fluids. Exosomal cargos have shown the potential to detect various types of cancers at early stages with high sensitivity and specificity. They can also delivery therapeutic agents efficiently. In this article, an overview of recent advances in the research of exosomal biomarkers and their applications in cancer diagnosis and treatment has been provided. Furthermore, the advantages and challenges of exosomes as liquid biopsy targets are discussed and the clinical implications of using exosomal miRNAs have been revealed.